Determination of Hydrocarbon Level in Distilled Water via Fiber Optic Displacement Sensor - Bidin, Noriah (Institute of Electrical and Electronics Engineers Inc., 2015)
Fiber optic displacement sensor offers a feasible way to detect hydrocarbon level in water. A reflective light intensity modulation technique is accomplished to detect hydrocarbon concentration in the ranges of 0%-20%. The reflective configuration technique enables the sensor to collect output voltage at a different displacement. The output voltage decreases linearly with hydrocarbon level at a corresponding optimized displacement of 1.5 mm. Linearity index close to one indicates that a high confident degree the sensor. Simple in design and low cost, makes this system as a promising sensor for determination of hydrocarbon level in water.